2018
DOI: 10.1186/s12906-018-2087-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of three conservative treatments in patients with lumbar spinal stenosis: lumbar spinal stenosis with acupuncture and physical therapy study (LAP study)

Abstract: BackgroundAlthough the efficiency of conservative management for lumbar spinal stenosis (LSS) has been examined, different conservative management approaches have not been compared. We have performed the first comparative trial of three types of conservative management (medication with acetaminophen, exercise, and acupuncture) in Japanese patients with LSS.MethodsPatients with L5 root radiculopathy associated with LSS who visited our hospital for surgical treatment were enrolled between December 2011 and Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…In contrast, Oka et al [28] asserted that acupuncture was significantly more effective than physical exercise according to the physical function score of the Zurich Claudication Questionnaire (ZCQ) and medication according to the satisfaction score. Hadianfard et al [29] reported acupuncture had a significant positive short-term effect on pain and quality of life in LSS patients.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Oka et al [28] asserted that acupuncture was significantly more effective than physical exercise according to the physical function score of the Zurich Claudication Questionnaire (ZCQ) and medication according to the satisfaction score. Hadianfard et al [29] reported acupuncture had a significant positive short-term effect on pain and quality of life in LSS patients.…”
Section: Discussionmentioning
confidence: 95%
“…[14,15] Acupotomy, as a kind of minimally invasive technique in CIM, has been used to treat various musculoskeletal diseases including LSS. [1822] This treatment has the advantage of simultaneously achieving the effect of conventional acupuncture and releasing pressure on the intervertebral disc by micro-incision of lumbar extensor muscle. [34]…”
Section: Discussionmentioning
confidence: 99%
“…Because it combines the effect of minimally invasive operation [14,15] using the small-knife with conventional acupuncture, [21,22] acupotomy is a promising candidate for the treatment of LSS. However, there have been no systematic reviews assessing acupotomy for the treatment of LSS.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hiroyuki [32] concluded that acupuncture was significantly more effective than physical exercise according to the physical function score of the Zurich Claudication Questionnaire (ZCQ). It was also more effective than medication, according to the satisfaction score.…”
Section: Discussionmentioning
confidence: 99%